2012
DOI: 10.3389/fnagi.2012.00031
|View full text |Cite
|
Sign up to set email alerts
|

Brain volumetric and microstructural correlates of executive and motor performance in aged rhesus monkeys

Abstract: The aged rhesus macaque exhibits brain atrophy and behavioral deficits similar to normal aging in humans. Here we studied the association between cognitive and motor performance and anatomic and microstructural brain integrity measured with 3T magnetic resonance imaging in aged monkeys. About half of these animals were maintained on moderate calorie restriction (CR), the only intervention shown to delay the aging process in lower animals. T1-weighted anatomic and diffusion tensor images were used to obtain gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…CR also considerably reduced stress reactivity (Willette et al, 2012c), where aged monkeys on CR showed less corresponding atrophy per point increase in a z-scored stress factor in many WM tracts, as well as similar amelioration in GM volume or microstructural density for orbital PFC and hippocampus. Finally, CR monkeys had many fewer perseverative errors and achieved task criterion in fewer trials for the most complicated Wisconsin Card Sort Test set-shifting tasks (Sridharan et al, 2012). Fewer errors corresponded to more GM in orbital PFC, an area where CR monkeys have more volume.…”
Section: 0 Discussionmentioning
confidence: 99%
“…CR also considerably reduced stress reactivity (Willette et al, 2012c), where aged monkeys on CR showed less corresponding atrophy per point increase in a z-scored stress factor in many WM tracts, as well as similar amelioration in GM volume or microstructural density for orbital PFC and hippocampus. Finally, CR monkeys had many fewer perseverative errors and achieved task criterion in fewer trials for the most complicated Wisconsin Card Sort Test set-shifting tasks (Sridharan et al, 2012). Fewer errors corresponded to more GM in orbital PFC, an area where CR monkeys have more volume.…”
Section: 0 Discussionmentioning
confidence: 99%
“…One type of inhibitory control involves the ability to modify behavior adaptively when contingencies change, and lesions to the prefrontal cortex impair this ability in humans and animals (Dias et al, 1996; Fellows and Farah, 2003; Rygula et al, 2010), suggesting that the prefrontal cortex is critical for the maintenance of flexible, goal-directed behaviors (Clarke et al, 2004). Indeed, individual differences in gray-matter volume within the prefrontal cortex are related to performance on tasks of inhibitory control in healthy humans and monkeys (Haldane et al, 2008; Tabibnia et al, 2011; Sridharan et al, 2012). The dorsal striatum also plays a critical role in inhibitory control processes (Bellebaum et al, 2008; Castane et al, 2010; Clarke et al, 2011), suggesting that inhibitory control relies on an integrated network of nuclei within the corticostriatal system.…”
Section: Introductionmentioning
confidence: 99%
“…Brain aging is also delayed by CR. MRI based studies of brain volume reveal preservation of white matter and neuronal volume, and markers of inflammation are significantly lower 13,37,38 . The caudate nucleus and putamen regions are vulnerable to age-associated atrophy and are protected by CR 13,39 .…”
Section: Caloric Restriction Impacts Health Indices In Rhesus Monkeysmentioning
confidence: 98%